2020
DOI: 10.1108/jsit-08-2019-0163
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the elderly and their next of kin’s usage of mobile personal safety service

Abstract: Purpose This study aims to understand elderly people and their family members’ perceptions and usage of a mobile personal safety service. Design/methodology/approach The study adopts both interviews and analysis of actual usage data to cross-validate the findings. Four family groups and 11 subjects participated in the study. Findings Elderly people are willing to learn to use the mobile safety service, and some elderly people explore more features than their younger family members. Family support facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The same survey reported that young people used this technology three times more than older proportions (Seybert and Reinecke, 2014). Säynätmäki and Zhang (2020) indicated that elderly users are willing to learn and use the technology compared to younger users, which reflects their perceptions of secure usage.…”
Section: Introductionmentioning
confidence: 98%
“…The same survey reported that young people used this technology three times more than older proportions (Seybert and Reinecke, 2014). Säynätmäki and Zhang (2020) indicated that elderly users are willing to learn and use the technology compared to younger users, which reflects their perceptions of secure usage.…”
Section: Introductionmentioning
confidence: 98%